Paradigma Mendidik dan Mengajarkan English For Specific Purpose dalam Meningkatkan Kompetensi Mahasiswa Akuntansi Ditinjau dari Perspektif Psikologi Pendidikan - Reni Marlina; Selvia Saefullah; Iin Indra Nuraeni; Agus Mulyanto; Suryana Sumantri (LP. Ma'arif Janggan Magetan, 2023)
In the field of education, the teaching paradigm means providing lessons about various sciences to individuals, which then will benefit the individual's thinking abilities. Educational Psychology is a branch of psychology that specializes in the understanding of learning and teaching processes in educational environments. Through the perspective of Educational Psychology, education can be viewed as a practical science that seeks to explain learning in accordance with scientifically established principles and facts surrounding human behavior. The research method used was descriptive qualitative with triangulation techniques, data collection through observation, interviews and questionnaires, as well as documentation studies. The results of this research are first, the presence of psychology in the world of education provides practical benefits in the teaching and learning process, especially in learning English For Specific Purposes (ESP) in Accounting courses, which helps students know English terms in making financial reports and journals. Second, it was found that the paradigm skills of teaching and educating ESP when viewed from educational psychology had a positive impact on college graduates and teaching staff. One of them is helping graduates have ESP competence in their field. It is hoped that the results of this research can contribute to the development of the ESP curriculum in Indonesia.